Specialization in Sport: How early... How necessary? - Stewart, C.; Susanj, D. (coachesinfo.com)
It was obvious by this limited study that additional information is needed to evaluate the risks and rewards of specialization before we as a global sport society offer a wholesale endorsement of its effectiveness. Due to the size and geographical limitations of this study, the outcomes cannot be extrapolated to other areas of the USA or the world. However, the fact that only 20% of varsity college basketball players in Montana had specialized in high school appears to argue against popular belief that specialization is necessary for athletic success. Additional studies in which researchers investigate the backgrounds of successful athletes would assist athletes, their parents, and coaches in determining if the need for specialization outweighs the risks.